EFFICACY OF HIGH-DOSE INTRAVENOUS STEROID TREATMENT IN METHANOL-INDUCED OPTIC NEUROPATHY: A SYSTEMATIC REVIEW - PERMAISUARI, NIZMA; RAHMAWATI, NUR AISYAH; NUSANTI, SYNTIA; THAMRIN, HUSNI (International Journal of Applied Pharmaceutics, 2019)
Objective: Methanol-induced optic neuropathy is a visual impairment that results from damage to the optic nerve fibers caused by methanol. It is frequently bilateral with permanent visual deterioration. According to the American Academy of Clinical Toxicology (AACT), methanol-poisoned patients who present with ocular manifestations should be treated with fomepizole, ethanol, or hemodialysis, which do not remove the metabolites from the optic nerve. High-dose intravenous steroid treatment has been proposed in several studies to salvage vision because of its anti-inflammatory effect. This article examines the existing literature on the efficacy of high-dose intravenous steroid treatment in patients with methanol-induced optic neuropathy. Methods: Literature searches were conducted using keywords and MeSH headings specifically chosen to identify published articles in CENTRAL, PubMed, ScienceDirect, ProQuest, EBSCO, and Google Scholar. Articles included were full-text, observational studies or randomized controlled trials published in English or Bahasa Indonesia. Results: Four case series and one case report were found in the bibliographic databases. We identified 33 patients with bilateral optic neuropathy caused by methanol ingestion who were initially treated with 1 g intravenous methylprednisolone, administered as a single dose or as divided doses for 3–4 d, followed by oral prednisolone. There were visual improvements in 48 out of 56 patients (83%). No adverse events were reported. Conclusion: Intravenous high-dose steroid treatment may benefit the visual status of patients with methanol-induced optic neuropathy. However, further studies are needed to determine the characteristics of patients who may benefit most from this regimen.